The effectiveness of the Montessori-based language arts program in children with mild mental retardation - Dacio, Liwayway S. (2007)
The development of reading among children serves as the umbrella for the entire Montessori Curriculum. This study attempted to prove the effectiveness of the Montessori-based language arts program in teaching children with mild mental retardation (CMMR) the basic reading skills specifically letter identification/sound production, phonemic awareness and word recognition. Data were analyzed using various statistical treatments namely: Wilcoxon-signed rank and Pearson product-moment correlation coefficients. It was confirmed that the Montessori-based language arts program is effective in teaching cildren the basic reading skills. The variables that correlated significantly with the reading performance of CMMR were the attendance of the respondents during the treatment and their attending skills.